Molecular characterization of an avian GA13-like infectious bronchitis virus full-length genome from Costa Rica - Villalobos Agüero, Ricardo Alberto (2021)
We describe the first whole-genome sequence of a GA13-like isolate of avian infectious bronchitis virus CK/CR/1160/16 (MN757859), obtained in 2016 in the province of Alajuela, Costa Rica. This virus caused an outbreak with great economic impact to the local poultry industry. The genome sequence is 27 696 bp in length, with the following genome organization 5′-UTR-Pol-S-3a-3b-E-4b-4c-M-5a-5b-N-6b-3′-UTR. The complete genome sequence has the highest sequence identity (94.03%) with DMV/1639/GA9977/2019 (MK878536) from Georgia, USA, and the lowest identity (86.03%) with ck/CH/LHLJ/08-6 (KX252788), from China. Analysis of the S1 subunit indicates that the Costa Rican isolate belongs to genotype I, lineage 17 (GI-17) and displays 96.89% identity with the S1 subunit of Ga-13/14255/14 (KM087780) (USA). Possible recombination events in genes S, E, M, 4b y 4c were detected, with Massachusetts, Connecticut, Arkansas and MA5 as potential parental types. This study highlights the importance of the epidemiological and molecular surveillance of avian infectious bronchitis.